Spatial Analysis for Mariculture Site Selection: A Case Study of Kukup Aquaculture Zones in the Peninsula of Malaysia - Chor, Wei-Kang; Lai, Teng-Yun; Mathews, Melissa Mary; Chiffings, Tony; Cheng, Chi-Wei; Andin, Victor Charlie; Lai, Kok-Song; Loh, Jiun-Yan (Frontiers in Marine Science, 2022)
Marine aquaculture sites at Kukup Strait in the peninsula of Malaysia are experiencing a decline in water quality in the last five years, resulting in high mortality rates (50 - 80%), seasonal massive fish mortalities and poor profitability. Currently, Kukup farmers are involved in intensive aquaculture within the existing aquaculture zone. This study explores the sustainability of a modern mariculture method, where fish farms are relocated to deeper waters with higher flushing rates, and high-density polyethylene (HDPE) are used to improve water quality. Several site selection criteria are utilised in identifying the proposed aquaculture industrial zone: 1) bathymetry depth (operational requirement: 10 m to 30 m), 2) located within the Kukup Port Limit, 3) does not interfere with the Kukup ferry navigation route, and 4) distance from Kukup mainland. Site feasibility analysis, including hydrodynamics, meteorology, water quality, sediment quality and macrobenthos assessment, was conducted to compare the proposed and existing aquaculture sites. It was found that the water quality at the existing site contained higher concentrations of fecal coliform and nutrients and salinity fluctuations. Tropical finfish can survive under these conditions with poorer fish health and higher fish mortality. Apart from that, the flushing capacity is higher in the proposed site, indicating the capacity to handle moderate-intensity aquaculture. Moderate-intensity aquaculture using HDPE cages could be profitable for the local fish farmers. Therefore, it is suggested that other locations within Kukup Straits with deeper waters (> 25 m) with possibly improved water quality and the ability for intensive aquaculture production should be explored for a larger depth and economics of scale.